Analysis Of Vo2max Physical Condition And Strength In Kurash Athletes In Makassar City - Hasyim (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aimed to describe the physical condition of male Kurash athletes in Makassar City based on two key physiological indicators: VO₂max and leg strength. A total of 15 athletes participated in the assessment, with data collected using the Multistage Fitness Test to estimate aerobic capacity and a leg dynamometer to measure lower-limb strength. The results were analyzed using descriptive statistics, including range, minimum, maximum, sum, and standard deviation. The findings showed that VO₂max values ranged from 39.9 to 45.2 ml/kg/min (SD = 1.63), while leg strength ranged from 120 to 145 kg (SD = 6.38). Classification analysis indicated that aerobic capacity varied more widely across athletes compared to leg strength, which tended to cluster in the moderate-to-high categories. These results suggest that individualized conditioning—particularly focused on improving aerobic fitness in lower-performing athletes—would be beneficial. Strength levels were relatively stable but still warranted targeted development for some athletes. The study recommends integrating high-intensity interval training and progressive strength programming to enhance overall performance, supported by contemporary evidence in combat sports conditioning.